PEREMPUAN-PEREMPUAN TANGGUH PENJAGA NILAI-NILAI KEISLAMAN ANAK: STUDI DAERAH MINORITAS MUSLIM - Muhammad Darwis Dasopang; Azmil Hasan Lubis (Kafa`ah: Journal of Gender Studies, 2021)
The first education that every child gets is family education. Mother is the figure in the family who has the most role in providing education. Islamic values must begin to be embedded in a person since he was a child, especially for those who live in Muslim minority areas. This is because these Islamic values can be eroded by environmental influences. This study aims to analyze the role of women in maintaining the Islamic values of children in the Muslim minority area of Labuan Rasoki. This topic is important because women play a big role in maintaining the Islamic values of children in the non-Muslim majority community. This research uses a qualitative approach with the type of case study. Data collection techniques are interviews and observations. The data obtained were analyzed by triangulation technique. The results showed that there were 3 roles that a mother takes in maintaining the Islamic values of their children, namely through non-formal education at Madrasah Diniyah Awaliyah (MDA), informal education in the family environment; and formal education in public and private schools. Housewives are among the women who continue to fortify their children's Islamic values through educational assistance, so that Islamic values persist in their children even though they live in Muslim minority areas.